2015
DOI: 10.1095/biolreprod.115.132209
|View full text |Cite
|
Sign up to set email alerts
|

The MicroRNA Signature of Mouse Spermatozoa Is Substantially Modified During Epididymal Maturation1

Abstract: In recent years considerable effort has been devoted to understanding the epigenetic control of sperm development, leading to an increased appreciation of the importance of RNA interference pathways, and in particular miRNAs, as key regulators of spermatogenesis and epididymal maturation. It has also been shown that sperm are endowed with an impressive array of miRNA that have been implicated in various aspects of fertilization and embryo development. However, to date there have been no reports on whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
197
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(212 citation statements)
references
References 66 publications
13
197
0
2
Order By: Relevance
“…Furthermore, epididymosomes can deliver RNAs to immature sperm (Sharma et al 2016). It also has been confirmed that the sperm RNA profile is altered during the epididymal maturation in mice (Nixon et al 2015) and that epididymosomes can directly facilitate such changes (Reilly et al 2016). Therefore, in addition to the testes, the epididymis may be an important origin of the sperm RNA.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, epididymosomes can deliver RNAs to immature sperm (Sharma et al 2016). It also has been confirmed that the sperm RNA profile is altered during the epididymal maturation in mice (Nixon et al 2015) and that epididymosomes can directly facilitate such changes (Reilly et al 2016). Therefore, in addition to the testes, the epididymis may be an important origin of the sperm RNA.…”
Section: Discussionmentioning
confidence: 86%
“…Alternatively, emerging evidence supports a direct influence of the environment on the epigenetic profile of spermatozoa. Environmental enrichment for 28 days, which accounts for the spermatogenic cycle of Mus musculus (Oakberg, 1956), could be altering the microRNA content of exosomes secreted by the epididymal epithelial cells which then fuse with the mature sperm in the caudal epididymis (Nixon et al, 2015a(Nixon et al, , 2015b. Environmental enrichment may be altering the dynamics of exosomal release and the microRNA content of these epididysomes, similar to its recently demonstrated impact on peripheral blood mononuclear cells (Pusic and Kraig, 2014;Pusic et al, 2016).…”
Section: Potential Mechanisms Mediating the Transgenerational Inheritmentioning
confidence: 87%
“…Maturing sperm undergo an extensive reorganization of sncRNA content in the epididymal tract, epitomized by both gain and loss of hundreds of miRNAs (Nixon et al 2015). This RNA remodeling probably occurs via interaction with RNA-rich extracellular vesicles shed from the epididymal epithelium (epididymosomes) (Belleannee et al 2013, Reilly et al 2016, Sharma et al 2016.…”
Section: Small Non-coding Rnamentioning
confidence: 99%